Expression, Purification, and Characterisation of Recombinant Alginate Lyase (Flammeovirga AL2) for the Bioconversion of Alginate into Alginate Oligosaccharides - Coleen E. Grobler; Blessing Mabate; Alaric Prins; Marilize Le Roes-Hill; Brett I. Pletschke (Molecules)
Alginate, a polysaccharide found in brown seaweeds, has regularly gained attention for its potential use as a source of bioactive compounds. However, it is structurally complex with a high molecular weight, limiting its application. Alginate oligosaccharides (AOS) are small, soluble fragments, making them more bioavailable. Alginate hydrolysis by enzymes is the preferred method for AOS production. Commercially available alginate lyases are limited, expensive, and sometimes exhibit unsatisfactory activity, making the search for novel alginate lyases with improved activity indispensable. The aims of this study were to codon-optimise, synthesise, express, purify, and characterise a recombinant alginate lyase, AL2, from Flammeovirga sp. strain MY04 and to compare it to a commercial alginate lyase. Expression was successfully performed using Escherichia coli ArcticExpress (DE3) RP cells, and the protein was purified through affinity chromatography. The recombinant enzyme was characterised by pH optimum studies, and temperature optimum and stability experiments. The optimal reaction conditions for AL2 were pH 9.0 and 37 °C, while for the commercial enzyme, the optimal conditions were pH 8.0 and 37 °C. At optimal reaction conditions, the specific activity of AL2 was 151.6 ± 12.8 µmol h−1 mg−1 protein and 96.9 ± 13.1 µmol h−1 mg−1 protein for the commercial alginate lyase. Moreover, AL2 displayed impressive activity in breaking down alginate into AOS. Hence, AL2 shows potential for use as an industrial enzyme for the hydrolysis of alginate into alginate oligosaccharides. Additional studies should be carried out to further characterise this enzyme, improve its purity, and optimise its activity.